2014
DOI: 10.1007/s00167-014-3499-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in acromial morphology of shoulders in patients with degenerative and traumatic supraspinatus tendon tears

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 39 publications
5
81
3
1
Order By: Relevance
“…In the present study, the morphological acromial differences between impingement and control patients indicate that the impinged acromia are more prominent anteriorly and inferiorly. These results were consistent with previous reports [12,16,17,24]. Nevertheless, these data could only support the correlation, but not the causal relationship, of acromial morphology and subacromial impingement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the morphological acromial differences between impingement and control patients indicate that the impinged acromia are more prominent anteriorly and inferiorly. These results were consistent with previous reports [12,16,17,24]. Nevertheless, these data could only support the correlation, but not the causal relationship, of acromial morphology and subacromial impingement.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, AT and AS were index of acromial inferior protrusion, AHI indicated the superior migration of humeral head, and LAA, AI, and CSA represented the lateral prominence of acromion [12,16,17,24]. However, the agreement for those parameters measured on X-rays was poor [11].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Miyazaki et al6) reported contrasting results obtained from two different races: the AI was a possible cause of rotator cuff tears only in a Brazilian population, not in a Japanese population. However, Moor et al10) and Balke et al14) recently described that distinct scapular morphologies including the AI accurately predicted the degenerative rotator cuff tear as radiologic parameters. Ames et al15) reported there was an association between the AI and the outcomes of arthroscopic rotator cuff repairs in 120 shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…Zumstein et al 20 identified a wide lateral extension of the acromion as a risk factor for re-tearing after open repair of massive tears. Balke et al 21 showed that shoulders with degenerative tears had a significantly larger lateral extension of the acromion than shoulders with traumatic supraspinatus tendon tears. Hamid et al 22 found excellent inter-observer reliability of the AI but no difference between patients with rotator cuff tears and individuals with no history of rotator cuff pathology.…”
Section: Acromion Shape In the Coronal Planementioning
confidence: 99%